Study on the Significance of Reduction to the Equator (RTE), Reduction to the Pole (RTP), and Pseudogravity in Magnetic Data Interpretation - Mira Nailufar Rusman; Susanti Alawiyah; Indra Gunawan (Postgraduate, University of Mataram, 2023)
Interpretation of geomagnetic anomaly data is challenging, due to the influence of the Earth's dipole magnetic field. In this study, we investigate the significance of employing methods to transform dipole anomalies into monopoles, aiming to enhance the interpretability of the data. Four methods were examined: Reduce to Pole (RTP), Reduce to Equator (RTE), and Pseudo-Gravity. The RTP method was implemented using general equations for RTP, Pseudo-inclination (PI), and Nonlinear thresholding (NTRTP). The computation programs for RTP and RTE were developed using the Matlab programming language. Synthetic models were constructed to investigate the effects of inclination values, object dimensions, and positions on the resulting magnetic anomaly response. The result shows that NTRTP methods give the best result with coefficient correlation >0.9. It can be used in every condition (low or high inclination). The implementation was conducted utilizing magnetic data in the Gunung Pandan geothermal area. The application of the reduced to the pole (RTP) technique on the field data successfully remove the dipole effects, and make interpretation process easier. Based on RTP map, the range of anomaly values spanning from -800 nT to 1000 nT. High anomalies were observed at the Gunung Pandan site, indicative of a probable intrusion of andesitic igneous rock.